Multivariable Analysis of Highly Pathogenic H5N1 and H5Nx Avian Influenza in Wild Birds and Poultry in Asian Subregions - Fatoyinbo, Hammed; Tiwari, Parul; Ip, Ryan; Miranda, Victor (Elsevier, 2025)
The spread of highly pathogenic avian influenza (HPAI) virus in wild birds, poultry, and other livestock worldwide has caused great concerns, especially in Asia, where the migration routes of many wild birds intersect with poultry farms. This often leads to interactions between wild and domestic birds during seasonal migration. These interactions influence the emergence and re-emergence of subclades and serotypes of avian influenza in Asia countries that are endemic to the disease. Using outbreak data from the Food and Agriculture Organization (FAO), we examine the geographical distribution of confirmed HPAI H5 cases in wild birds and poultry across Asia between January 2004 and August 2024. H5N1 is the most prevalent serotype among all HPAI H5 serotypes reported, followed by H5N8. The temporal analysis reveals three waves of outbreaks across Asian regions: an initial peak in 2004–2005, a second wave around 2009–2011, and a third, more recent wave, from 2017 to 2023. Multivariable Poisson regression models were used to assess the geographical, seasonal and yearly patterns of confirmed HPAI H5 cases among different categories of birds. The results indicate that these factors significantly influence the prevalence of HPAI H5, with a higher risk of H5N1 in Southeast Asia and H5N8 in East Asia, particularly during the winter and in poultry, as compared to wild birds. Our findings highlight the need for targeted surveillance, risk-based management, and coordinated interventions to mitigate the spread of HPAI H5 in high-risk areas. This study provides valuable insights that could be used to improve biosecurity measures and inform policies for the effective control and prevention of HPAI outbreaks in Asia.
Keywords: 06 Biological Sciences; 07 Agricultural and Veterinary Sciences; 11 Medical and Health Sciences; Immunology; 3009 Veterinary sciences; 3107 Microbiology; 3204 Immunology; Avian influenza; H5 HPAI; Wild birds; Poultry